2023
DOI: 10.3934/jimo.2022194
|View full text |Cite
|
Sign up to set email alerts
|

Optimal investment strategies for asset-liability management with affine diffusion factor processes and HARA preferences

Abstract: <p style='text-indent:20px;'>This paper investigates an optimal asset-liability management problem within the expected utility maximization framework. The general hyperbolic absolute risk aversion (HARA) utility is adopted to describe the risk preference of the asset-liability manager. The financial market comprises a risk-free asset and a risky asset. The market price of risk depends on an affine diffusion factor process, which includes, but is not limited to, the constant elasticity of variance (CEV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Zhang and Zhao [15] studied the optimal reinsurance-investment problem related to sparse risk based on the HARA utility function, in which the CEV model drove the price of risky assets, and they obtained the closed-form expression of the optimal strategy. Zhang [16] studied the optimal asset-liability management problem under the framework of maximizing the expected utility, taking a variety of stochastic volatility models as a particular case and using the backward stochastic differential equation (BSDE) method to derive closed-form expressions for optimal investment strategy and optimal value function. Through the research literature, it was found that the HARA utility function was more widely used than the logarithmic utility function, exponential utility function, and power utility function.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Zhao [15] studied the optimal reinsurance-investment problem related to sparse risk based on the HARA utility function, in which the CEV model drove the price of risky assets, and they obtained the closed-form expression of the optimal strategy. Zhang [16] studied the optimal asset-liability management problem under the framework of maximizing the expected utility, taking a variety of stochastic volatility models as a particular case and using the backward stochastic differential equation (BSDE) method to derive closed-form expressions for optimal investment strategy and optimal value function. Through the research literature, it was found that the HARA utility function was more widely used than the logarithmic utility function, exponential utility function, and power utility function.…”
Section: Introductionmentioning
confidence: 99%